STUDY OF WATER QUALITY AND SIMULATION CHROMIUM (CR) TRANSPORT IN SURFACE WATER (STUDY CASE IN DELI RIVER, MEDAN) - HARPAH HASIBUAN , NOVRIDA
Deli River is one of the main rivers which crosses Medan.The development of industries and domestic waste along the Deli River basin have affected the quality of water and sediment. According to the Environment Agency, North Sumatra, there are approximately 54 industries and 27 domestic sewers. These industries are dominated by industries that produces organic waste and heavy metals such as paints industry, armored industry, iron smelting, etc.. Therefore, in this study the reviewed pollutant parameters are pH, temperature, DO, COD, BOD and Cr in order to determine Water Pollution Index. To determine the spread of chromium along Deli River, the mathematical modeling was carried out using one-dimensional analytical model using flug flow equation. The research was conducted at the Deli River in Medan. Based on the results Deli River was polluted in terms of the high BOD5‘s value. The results of water quality index also showed that for the Class II water designation, then lightly polluted Deli River. The result from analysis sensitivity showed that kd1 was the most affected parameter towards coefficient sensitivity(S) = 0.0145. Calibration’s result with kd1= 0.1 m3/g in water showed that lower value error as 0.0092. Calibration’s result with kd1=0,02m3/g in sediment showed that lower value error as 1,56. Simulation result of chromium concentration was close enough to the observed concentration. The result of DO simulation with Streeter-Phelps showed that ka=1,1/day and kd= 0,35/day and the result of dissolved oxygen was close enough to the observed concentration as well.